2019
DOI: 10.3389/fnins.2019.01219
|View full text |Cite
|
Sign up to set email alerts
|

A Masked Aversive Odor Cannot Be Discriminated From the Masking Odor but Can Be Identified Through Odor Quality Ratings and Neural Activation Patterns

Abstract: Odor masking is a very prominent problem in our daily routines, mainly concerning unpleasant sweat or toilet odors. In the current study we explored the effectiveness of odor masking both on a behavioral and neuronal level. By definition, participants cannot differentiate a fully masked unpleasant odor from the pleasant pure odor used as a masking agent on a behavioral level. We hypothesized, however, that one can still discriminate between a fully masked odor mixture and the pure masking odor on a neuronal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…However, it is also possible that the compounds responsible for the additional leather‐like impression in vehicle 1 masked the odor impression green. In literature, there are numerous reports of such masking effects in complex smell mixtures 26 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also possible that the compounds responsible for the additional leather‐like impression in vehicle 1 masked the odor impression green. In literature, there are numerous reports of such masking effects in complex smell mixtures 26 …”
Section: Discussionmentioning
confidence: 99%
“…In literature, there are numerous reports of such masking effects in complex smell mixtures. 26 Moreover, several fatty/cardboard-like smelling compounds were identified in all samples, including the unsaturated al- It is interesting to note that the concentrations of the quantified unsaturated aldehydes were very low, and, as a consequence, it was not always possible to generate unambiguous mass spectra of these aldehydes.…”
Section: -Ethylidene-2-norbornenementioning
confidence: 99%
“…Olfactory adaptation resulting from constant exposure to perfume fragrance is one of the two plausible reasons contributing to the diminished threshold and discrimination performances under both fragrance conditions. The other reason, related to a lowered olfactory performance under the fragrance conditions, would be a masking effect because of the personal fragrance, notably in the excessive condition, possibly masking the lower-intensity scents from the Sniffin' Sticks test [31,32]. It should be noted that in the methodology used by the Sniffin' Sticks TDI set, the odor threshold task was conducted first, suggesting that the findings here might be related to the possible diminution of the olfactory capabilities minutes after being exposed to the scent.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the odor sticks used for the threshold or discrimination tasks, the odor sticks used for the odor identification tasks exhibited stronger odor intensities and a greater number of unique odors, thereby lessening the effect of the perfume fragrance on the odor identification performance. Olfactory adaptation research has indicated that such adaptation may only influence scents of lower intensity, meaning that the more highly intense scents of the odor identification sticks had no issues with respect to being detected by participants in the fragrance treatments [32,33]. Other studies also indicate that identification and discrimination tasks involve two different cognitive processes, thus offering additional insight as to why performance differences were not seen in the identification task between the fragrance conditions [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the odor profile analysis enables the perception of a specific odor difference of two or more samples by indicating the presence or absence of specific substance classes or single odorants [82]. In the case of complex odor mixtures, however, individual odor descriptions cannot necessarily be assigned to individual compounds, since several individual odorants can be responsible for the respective odor impression due to additive, suppressive or synergistic effects [83,84]. Therefore, instrumental analytical methods are used to characterize the underlying odor-active substances systematically.…”
Section: Human Sensory Evaluation Methods For the Characterization Of...mentioning
confidence: 99%